Promoción y prevención en salud oral dirigido a niños del grado primero de básica primaria del colegio Carlos Ramírez Paris sede principal - Silva Ortíz, Marlyn Estrella; Sachica Barrera, Erika Zuleny (Universidad Antonio Nariño, 2023)
Initially, the work was shared with the first grade students, their parents and teachers, defining the processes to follow, then proceeded to identify the prevalence of caries in the selected children, through the application of non-invasive dental procedures that do not carry any risk. , such as the COP Index, which is an index to identify the presence of decayed teeth, filled teeth and missing teeth, and the Silness and Löe Plaque Index, which allows establishing degrees of intensity of plaque accumulation.